PEMIKIRAN EKONOMI ISLAM IBN TAIMIYAH - Hairani, Hairani; Andini, Nisha (CV. Pusdikra Mitra Jaya, 2025)
Ibn Taimiyah provides an answer for the State in terms of the market mechanism, which is to become a post for deep quality improvement to make its people aware of the importance of moral standards and moral quality as a rule of progress and can make it happen in financial life. An Ibn Taymiyyah is of the view that looking at the market mechanism is actually not limited to monetary issues, more than that it includes several parts of state and religious life.